Association Between Sleep Quality and Proprioception in Young Adults: Sleep Quality and Proprioception in Young Adults - Arshad, Khadija; Sukhera, Sadia; Mehboob, Saiba (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2024)
Sleep is a vital biological process that enables us to function cognitively, emotionally, and physically. However, rising academic and lifestyle expectations have caused widespread poor sleep quality among young adults. Objectives: To investigate the relationship between sleep quality and proprioceptive performance in healthy young people. Methods: A cross-sectional survey of 171 university students aged 18-25 years was conducted using purposive sampling. The Sleep Quality Scale (SQS) was used to assess sleep quality, and the Proprioceptive Performance Questionnaire (PPQ) to evaluate proprioceptive performance. Descriptive statistics were employed to investigate demographic variables, while chi-square analysis was done to assess the connection between sleep quality and proprioception. Statistical significance was determined at p<0.05. Results: The study had 171 participants. A considerable number (81.3%) had poor sleep quality, and 38% had decreased proprioceptive awareness. A chi-square analysis revealed a statistically significant link between poor sleep quality and decreased proprioceptive function (p=0.026), which impacted balance, joint position perception, and force modulation. Conclusions: These findings point to a significant link between poor sleep quality and decreased proprioceptive performance in young people. Poor sleep quality can alter sensorimotor integration, increasing the risk of postural instability and motor coordination deficiencies in otherwise healthy people.